Milho crioulo e melhorado: tolerância a deficiência hídrica na perspectiva da segurança e soberania alimentar - Langner, Josana Andreia (2018)
The objectives of this thesis were to (i) discuss the importance of maize crop nowadays and its crucial role in the future for food production in scenarios of water defcit, and its importance in the conservation of landrace cultivars, which hold a considerable part of this reserve of genetic variability and (ii) to compare the tolerance to water defcit of improved and landrace, maize cultivars in the field and in rain exclused environment and to determine FATS threshold in the reproductive period. Information from the temperature shows that in several places, with the aid of the Genetic Improvement, the characteristic of plants that lead to drought tolerance were established. It is concluded that for a cultivar to be accepted by the farmers, in addition to the adaptation characteristics, it must have a high grain yield and information needs to be disclosed. To quantify the tolerance of local cultivars, field experiments were conducted in the 2015/2016, 2016/2017 and 2016/2017, 2017/2018 growing season for FTSW in the experimental area of the Plant Science Department at UFSM, Santa Maria, RS. The landraces cultivars presented similar yield in the irrigated and non irrigated system, while the improved cultivars increased yield in the irrigated. For FTSW, 'AS 1573PRO' and 'Cinquentinha' presented similar values in the first year, and 'Bico de ouro' was smaller. In the second year 'AS 1573PRO' presented FTSW, followed by 'Cinquentinha' and again smaller 'Bico de ouro'. The cultivar 'AS 1573PRO' had the highest tolerance indicated by FTSW, in a short period of deficiency. The 'Cinquentinha' showed a smaller tolerance for FTSW, but as indicated by gas exchange measurements under conditions with prolonged water stress, it is more tolerant, producing ears with grains even under extreme conditions of water deficit in the FATS experiment.